2005
DOI: 10.1021/jo050031i
|View full text |Cite
|
Sign up to set email alerts
|

Ortho-Selective Direct Cross-Coupling Reaction of 2-Aryloxazolines and 2-Arylimidazolines with Aryl and Alkenyl Halides Catalyzed by Ruthenium Complexes

Abstract: The ortho position of the aromatic ring in 2-aryloxazolines and 2-arylimidazolines is selectively arylated and alkenylated with organic halides in the presence of a ruthenium(II)-phosphine complex. In the case of unsubstituted and para-substituted phenyloxazolines, 1:2 coupled products were obtained preferentially, while 1:1 coupled products were obtained in the case of meta-substituted phenyloxazolines and N-acylarylimidazolines. The reaction is proposed to proceed via the generation of an organoruthenium int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
77
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(81 citation statements)
references
References 41 publications
1
77
0
3
Order By: Relevance
“…Ruthenium catalyzed chelation assisted ortho-arylations of (2-pyridyl)arenes and acetophenone imines with aryl chlorides [378]. Related ruthenium-catalyzed ortho-arylations and -alkenylation of 2-aryloxazolines and 2-arylimidazolines were described [379]. Regioselective chelation-directed alkylation of sp 3 -carbon-hydrogen bonds of 2-alkylpyridines with aryl iodides was reported (Eq.…”
Section: Carbon-carbon Bond-forming Reactions Using Terminal Alkynes mentioning
confidence: 99%
“…Ruthenium catalyzed chelation assisted ortho-arylations of (2-pyridyl)arenes and acetophenone imines with aryl chlorides [378]. Related ruthenium-catalyzed ortho-arylations and -alkenylation of 2-aryloxazolines and 2-arylimidazolines were described [379]. Regioselective chelation-directed alkylation of sp 3 -carbon-hydrogen bonds of 2-alkylpyridines with aryl iodides was reported (Eq.…”
Section: Carbon-carbon Bond-forming Reactions Using Terminal Alkynes mentioning
confidence: 99%
“…In the case of 7, the reaction took place efficiently without adding KF. It is cited that related mono-and diarylation reactions of these substrates with aryl halides or tosylates have been reported [20][21][22][23].…”
Section: Resultsmentioning
confidence: 99%
“…In general, C-H functionalization proceeds via metallacycle formation by oxidative addition of transition-metal and subsequent coordination of nucleophile and reductive elimination. Recent research has revealed that nitrogen-containing functional groups such as pyridines [14][15][16], imines [17][18][19], oxazolines [20,21], and amidines [22] effectively act as directing groups for regioselective C-H functionalization.…”
mentioning
confidence: 99%
“…Inoue and co-workers have reported ortho-selective arylation of 2-arylimidazolines with aryl halides in the presence of a Ru(II)-phosphine complex [22] 5 For a review on Cu-mediated C-H functionalization, see [23]. 8 2 Development of Divergent Synthetic Methods of Pyrimidobenzothiazine 2-phenylimidazoline 13 with 1.2 equiv of bromobenzene using [RuCl 2 (g 6 -C 6 H 6 )] 2 yielded the mono-and diarylated products (14 and 15) in a 64 % yield and in 31:69 ratio (eq 1).…”
mentioning
confidence: 99%